Texturização superficial eletroquímica sem mascaramento com finalidades tribológicas - Parreira, Jakeline Guimarães (2011)
Surface texturing can be used to improve the tribological performance of mechanical contacts, in particular in the case of lubricated systems. The purpose of this work is to improve an alternative method for surface texturing based on electrochemical machining. Electrochemical dissolution combines high speed, good reproducibility and high cost-benefit ratio, which are important factors when an industrial application of surface texturing is pursued. Since the area to be textured is not required to be masked, the technique is optimized, without the need of a pre or post treatment of each surface. Another nonconventional machining technique, Electrical Discharge Machining (EDM), was used to drill microholes in the cover of the tool that will be used in the microtexturing operations. The pattern of microholes in the tool is copied onto the workpiece through the action of electrochemical dissolution. The improvement of the electrochemical texturing technique was achieved with the design of an electronic circuit with a data acquisition system and of an electrochemical cell and with the specification of the electrolyte pumping system, which improved the surface finish of the textured workpiece, as well as with the development of tools that made possible the confection of different microtexture patterns. In the electrochemical cell, the tool material was AISI 230 ferritic stainless steel and the workpiece material was carbon steel AISI 1010o. Sodium Chloride was chosen as the electrolyte tool makes the electrical contact between the electrodes. During the electrochemical texturing tests, the effect of important parameters such as the gap between electrodes, the applied voltage and the total texturing time were evaluated, and the best values found were a gap of 100 mm, a voltage between 30V and 40V and a texturing time between 20s and 60s. Different texturing patterns were obtained with good results, including dots, trace-dots and chevrons. A tribological test showed a reduction in friction and wear of a textured surface lubricated with MoS2, when compared with a smooth surface.